Model Pertunjukan Ludruk Sinema: Wahana Pengembangan Ludruk Jawa Timur - Astrid Wangsagirindra Pudjastawa; Bagus Baghaskoro Wisnu Murti (Mahesa Research Center, 2022)
There is a problem that underlies this researcher to do that, namely the interest of the younger generation in the art of ludruk is decreasing and it is feared that it will have an impact on the extinction of one of the various performing arts in Indonesia. This study aims to describe the ludruk cinema performance model, which is a new creative innovation offered to answer various problems of ludruk art. The learning method used is Design Thinking which consists of seven main stages, namely: (1) define, (2) research, (3) ideate, (4) prototype, (5) select, (6) implement and (7) learn. In the results and discussion section, the researcher describes (1) the concept of the Ludruk Cinema Performance, (2) the structure of the Ludruk Cinema Performance, and (3) the Ludruk Cinema Performance Model: A Forum for the Development of the Ludruk Cinema in East Java Cinema. The ludruk art development model is still strived to contain character values, with novelty carried out in the form of performances that are expected to be in accordance with the times.